Multiple chitinase enzymes from a single gene of Bacillus licheniformis TP-1 - Srisurang Tantimavanich (2018)
Three chitinase activity bands in a culture supernatant of Bacillus licheniformis TP-1 were detected by non-denaturing PAGE. They were designated chitinase bands 1, 2, and 3 in order from the gel origin. Analysis by immunodiffusion and immunoelectrophoresis using polyclonal antibody raised against chitinase band 3 indicated that these chitinases were antigenically similar. B. licheniformis TP-q and Escherichia coli harboring the cloned chitinase gene (pCHIL3) from strain TP-1 expressed 3 chitinase bands by non- denaturing PAGE and SDS-PAGE which gave estimated molecular masses of 68, 62, and 50 kDa (named Chi68, Chi62, and Chi50, respectively). All three chitinases had the same N-terminal amino acid sequences, strongly suggesting that Chi62 and Chi50 were derived from Chi68 by a processing step(s) at the C-terminus. The deduced C-terminal amino acid sequence of Chi68 showed homology to amino acid sequences of known chitin and cellulose binding domains. Chi62 and Chi50 lacked this domain (judging from their deduced amino acid sequences and calculated molecular masses) and they were unable to bind chitin, suggesting that they were generated from Chi68 by cleavage of the chitin binding domain at the C-terminus. Comparison of chitinase activities indicated that this binding domain was important for complete hydrolytic activity towards colloidal chitin.